PENERAPAN PERANGKAT LABORATORIUM IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR DI DAERAH TERPENCIL - Werdhiana, I Komang; Wahyono, Unggul (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
Learning in remote areas needs attention regarding the use of laboratory equipment. Laboratory equipment is needed in science learning. Therefore, the purpose of this research was to apply science laboratory equipment to improve the learning outcomes of elementary school students in remote areas. This study used an experimental method with a one-group pretest-posttest research design and was conducted in three elementary schools in Donggala Regency, namely SDN 3 Labuan Toposo, SDN 27 South Banawa, and SDN 7 Rio Pakava. The students involved in the research were 14 students at SDN 3 Labuan Toposo, 11 students at SDN 27 Banawa Selatan, and 27 students at SDN 7 Rio Pakava. Learning begins with giving an initial test (pretest), after learning a final test (posttest) is given and students are asked to fill out an interest questionnaire. The test results showed an increase from pretest to posttest. Students have a high interest in learning science by using laboratory equipment. This means that science laboratory equipment has a positive impact on science learning for elementary schools in remote areas.